Gestão patrimonial no setor púbico: análise das rotinas do Instituto Federal de Sergipe à luz das NBC T 16.9 e NBC T 16.10. - Costa, Gustavo Barros (2017)
For many years the concern with public patrimony was restricted to what had been purchased and its monetary value. In order to control the state action and the public manager’s initiatives, some control mechanisms were instituted purposing to ensure the operation within the limits imposed by legislation and thus meeting collective interests and good management practices. In the Instituto Federal de Sergipe (IFS), the reality is similar to a large number of government agencies in which they present deficient equity controls, as well as the accounting aspects that are not fully fulfilled. This research aims to analyze the asset control of movable property in IFS in its various campi in relation to current legal and accounting regulations. The research is classified as exploratory, descriptive, bibliographic, documentary, applying an online questionnaire that is composed of closed and discursive questions. The data treatment was performed using simple descriptive statistics and content analysis. The organizational intervention, through the action plan, used the Analysis and Problem Solving Methodology (MASP), which is based on the PDCA cycle, together with the stratification management tools, tree diagram and 5W2H. It is verified that the patrimonial control is important and necessary not only to comply with the legal precepts, but also to demonstrate the reality of the organization in a reliable way, besides reflecting the care with the public assets which were acquired with the resources of all taxpayers. The results presented consonance and dissonance regarding the accounting procedures, and for these, after the organizational diagnosis, some action plans were proposed with the purpose of pointing out the solutions to the situations identified.